1976
DOI: 10.1139/x76-036
|View full text |Cite
|
Sign up to set email alerts
|

Cartographie du risque de retrouver de la mortalité dans les forêts de sapin baumier attaquées par la tordeuse des bourgeons de l'épinette

Abstract: A hazard rating map is obtained in Quebec by superimposing the map of the annual damage caused by the spruce budworm, Choristoneurafumiferana (Clem.), during the past 4 years on that forecast for the next year. The various levels of risk are based on the physiological value of each year of foliage production and the ability of balsam fir, Abiesbalsamea Mill., to resist repeated budworm attacks. Applied to the forest of Quebec, this hazard map can lead to a more rational use of pesticides against the budworm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Fuentealba et al. () suggested that RPC could be used to better estimate the effects of damage by SBW than the measures of defoliation used in short‐term studies because RPC is less sensitive to fluctuations in SBW population (Hardy and Dorais ). We did not observe a direct relationship between AD and NEP; however, there was a clear inverse relationship between AD DS1 and NEP DS1 for all forest types early (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuentealba et al. () suggested that RPC could be used to better estimate the effects of damage by SBW than the measures of defoliation used in short‐term studies because RPC is less sensitive to fluctuations in SBW population (Hardy and Dorais ). We did not observe a direct relationship between AD and NEP; however, there was a clear inverse relationship between AD DS1 and NEP DS1 for all forest types early (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…While defoliation thresholds used to determine when Btk should be applied vary provincially, spraying often occurs only after substantial defoliation is detected. For example, in Québec, aerial spraying is applied only after one year of moderate‐to‐severe SBW defoliation (Hardy and Dorais , Bauce et al. , Fuentealba et al.…”
Section: Introductionmentioning
confidence: 99%
“…The new protection policy aimed at protecting at least 50% of current year foliage to keep trees alive. This foliage protection target was based on the study of Hardy and Dorais (1976), which used the estimated contribution made by the various ages of foliage to the total photosynthetic capacity of balsam r reported by Clark (1961) to evaluate the capacity of balsam r to recover after spruce budworm defoliation. Their results suggest low balsam r mortality when 38 to 51% of its photosynthetic capacity is maintained by the end of the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dorais et al (1995), 80% of treated areas were adequately protected in terms of foliage protection 10 out of 14 years between 1974 and 1987 which demonstrate that the spraying operations conducted in Quebec met the protection goal. Despite the good results in terms of foliage protection and the link between the aforementioned variable and tree mortality (Hardy and Dorais 1976), there exists little information on the long-term e cacy of aerial applications of insecticides in reducing budworm-related tree mortality. For example, an early study reported that sprayed stands with DDT exhibited 11% mortality rate (2% of the basal area) whereas tree mortality reached 44% (44% of basal area) in unprotected stands (Batzer 1973).…”
Section: Introductionmentioning
confidence: 99%
“…), un insecte defollateur du sapin baumier, Abies balsamea Mill., et des epinettes blanche et rouge, Plcea glauca Voss et P. rubens Sarg., est consideree par certains comme I'ennemi numero un au niveau economique des for& resineuses du nord-est de I'Amerique (Miller, 1975). Des epidemies repetees, (Blais, 1965;Swaine et Craighead, 1924), et une tendance de ces dernieres a revenir intervalles plus courts (Blais, 1974) ont ete a I'origine de nombreuses etudes sur la biologie de I'insecte, (Mitchell et Seabrook, 1970), la susceptibilite des forBts (Blais, 1968;Hardy et Dorais, 1976;Morris et Bishop, 1951) et I'epidemiologie (Blackman, 1919;Blais 1964). Toutefois, rares sont les etudes d'impact sur le milieu forestier (Baskerville et MacLean, 1979;Batzer, 1973;Bla~s 1981;McLlntock, 1955), malgre de nombreux estlmes lmprec~s (Baskerville, 1960, Blals, 1958Morris, 1946).…”
Section: Introductionunclassified